Summer and Autumn Movements of Belugas of the Eastern Beaufort Sea Stock - Richard, P.R.; Martin, A.R.; Orr, J.R. (ARCTIC, 2001)
Beluga whales of the eastern Beaufort Sea stock were tagged with satellite-linked time-depth recorders and tracked during summer and autumn in 1993, 1995, and 1997. Whales occupied the Mackenzie estuary intermittently and for only a few days at a time. They spent much of their time offshore, near or beyond the shelf break and in the polar pack ice of the estuary, or in Amundsen Gulf, M'Clure Strait, and Viscount Melville Sound. The movements of tagged belugas into the polar pack and into passages of the Canadian Arctic Archipelago suggest that aerial surveys conducted in the southeastern Beaufort Sea and Amundsen Gulf may have substantially underestimated the size of the eastern Beaufort Sea stock. Ranges of male and female belugas were somewhat segregated in two of the three years of study. In late July of 1993 and 1995, most males were located in Viscount Melville Sound, while females were primarily in Amundsen Gulf. Movement patterns of males tagged in late July in 1997 were different from those of males tagged in early July in 1993 and 1995. In September, belugas migrated westward along the continental shelf and farther offshore in the Alaskan Beaufort Sea. The tracks from 1997 show that the western Chukchi Sea is an autumn migratory destination and that at least some belugas continued their migration south towards the Bering Strait in November. Some conclusions from this study about beluga ecology challenge conventional wisdom, in that estuarine occupation appears to be short-lived, belugas travel long distances in summer to areas hundreds of kilometres from the Mackenzie Delta, and they do not avoid dense pack ice in summer and autumn. Durant l'été et l'automne 1993, 1995 et 1997, on a effectué des suivis télémétriques par satellite de bélugas du stock de la mer de Beaufort orientale. Ces cétacés ont occupé l'estuaire du fleuve Mackenzie de façon intermittente, n'y restant que quelques jours à chaque fois. Ils ont passé la plupart de leur temps au large de l'estuaire, près de la pente continentale et ...